Lectins as possible tools for improved urinary bladder cancer management. (12th February 2019) - Višnjar, Tanja; Romih, Rok; Zupančič, Daša
Abstract: Urinary bladder cancer is the ninth most common cancer in developed countries with poor prognosis and outcome for the patient due to the challenging diagnosis and limited treatment possibilities. Bladder cancer arises mainly from urothelial cells lining the lumen. Urothelial cells form a three- to five-layered urothelium, which maintains the blood–urine barrier. The carbohydrates that cover the apical surface of superficial urothelial cells, i.e. umbrella cells, are crucial for this function. The composition of the carbohydrate covering is altered during urothelial cancer transformation. These bladder cancer-associated carbohydrate changes are a promising field for diagnosis, therapy and management. Lectins, which are carbohydrate-binding proteins, can be used to detect subtle alterations in carbohydrate composition during urothelial cancer transformation. Extensive research into various lectin applications has already been conducted, but the results are often contradictory and confusing. None of these applications have reached clinical trials. We review the literature and discuss (i) current bladder cancer management, (ii) lectin-based assays for detection of various cancer subtypes, (iii) lectin-based strategies for innovative bladder cancer treatment and finally (iv) lectins in nanotheranostics for personalized bladder cancer management.